INTRODUCTION TO SIAMESE ORANGE PROCESSING METHOD IN ORDER TO AVOID BITTER TASTE - Nur Hidayat; Sakunda Anggarini; Sri Suhartini; RirisWaladatun Nafi’ah (Ann Publisher, 2023)
Sumbersekar is part of Dau Regency, which is a region famous for the production of fruits,vegetables, and flowers because it is located in a high area with a cold climate. Sumbersekar regionhas a variety of agricultural products, including superior vegetables and fruits. One of the leadingproducts is Siamese orange (Citrus nobilis). The problem that farmers must face is that the sellingprice of Siamese orange honey often drops during the high harvest season, which frequently harmsfarmers. When the selling price drops, many oranges are left on the tree and unprocessed due to theunknown processing technology of the oranges. One of the efforts to overcome excess unsold harvestis to carry out post-harvest processing. Processed processing of Siamese honey is an alternativeprocess because it is easy. However, the weakness of processing oranges made by domestic scaleindustries is that they still have a bitter taste so consumers do not like them. Therefore, introducingcitrus processing methods to avoid bitterness must be promoted so that their products have goodcompetitiveness in the market. The solution provided by the UB team is to provide training activitieson how to produce good processed citrus products and introduce good packaging technology. Thus,farmers in Sumbersekar Village can improve the quality of their processed Siamese citrus productsand compete better in local and regional markets. This will help increase farmers' incomes and reducelosses as the selling price of oranges falls during high harvests.